Factors of Using Long Acting and Permanent Methods (LAPM) of Contraception: Bangladesh Perspective (Dhaka University Journal of Science, 2023)
The Government of Bangladesh is very much aware of controlling excessive birth rate to maintain population problem. Though Bangladesh is owning self-sufficiency in many sectors, the increasing population is a great impediment for the development of the country. So, promoting different contraceptive methods is of much importance. This work aims at identifying the important determinants that affect the long-acting and permanent methods (LAPM) of contraception. Firstly, chi-square test of association is carried out for defining the correlates of LAPM of contraception using Bangladesh Demographic and Health Survey (BDHS), 2017-18 data. For estimating the effects of each controlled independent variables, data are further analyzed within a multivariate framework. To obtain consistent and efficient estimates of parameters of interest, multinomial logistic regression model is used in this work. The study finds several socio-economic and demographic variables having high impact on using LAPM. The study findings are properly discussed and recommendations are made accordingly for the policy makers.Dhaka Univ. J. Sci. 71(2): 87-94, 2023 (July)